2002
DOI: 10.1152/ajplung.00140.2001
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced lung injury in neonatal rats: changes in gelatinase activities and consequences on lung growth

Abstract: Postnatal lung growth disorders may involve imbalance between metalloproteinases and their inhibitors. Inflammatory cell 92-kDa gelatinase overactivity has been reported in adults with lung injury but has not been looked for in neonates. We compared gelatinase activity in neonatal and adult rats and evaluated postnatal lung growth after lipopolysaccharide (LPS)-induced lung injury. Significant intra-alveolar inflammatory cell recruitment occurred in adults and neonates; cell counts increased 16-fold in adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…Thus MMP-9 may be considered as an important marker of the initial inflammatory response, but its contribution to the development of long-term sequel is uncertain. These findings are in complete agreement with our laboratory's recent experiments performed in newborn rats (14). Indeed, we found that alveolar growth disorders induced by intratracheal instillation of lipopolysaccharide were associated with alveolar neutrophil influx and increased MMP-9 level, but we failed to prevent growth disorders by inhibiting MMP-9 activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus MMP-9 may be considered as an important marker of the initial inflammatory response, but its contribution to the development of long-term sequel is uncertain. These findings are in complete agreement with our laboratory's recent experiments performed in newborn rats (14). Indeed, we found that alveolar growth disorders induced by intratracheal instillation of lipopolysaccharide were associated with alveolar neutrophil influx and increased MMP-9 level, but we failed to prevent growth disorders by inhibiting MMP-9 activity.…”
Section: Discussionsupporting
confidence: 93%
“…Once secreted, MMP-9 can be activated by many products present in inflammatory airways, especially oxidants (29) and neutrophil elastase (34). In our study, the presence and amount of (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Values are medians with 25th-75th percentiles in parentheses; n, no. of neonates.…”
Section: Discussionmentioning
confidence: 73%
“…20 fields per animal) selected by systematic sampling from a random starting point to ensure that the sections were randomly distributed throughout all of the lung lobes. We used a correcting factor of 1.22 to correct the surface area values for the shrinkage caused by our fixation and paraffin-embedding procedure (20). Using the point and intersection counting method (19) …”
Section: Methodsmentioning
confidence: 99%
“…Morphometric evaluations were repeated by a second independent observer in order to test reproducibility. To correct for shrinkage associated with fixation and paraffin processing, area values were multiplied by 1.22, a factor calculated during a previous evaluation [17]. All morphometric data were expressed as relative and absolute values, as described by BURRI et al [18].…”
Section: Assessment Of Lung Morphometrymentioning
confidence: 99%
“…Assessment of inflammation BAL BAL was performed as previously described [17]. Briefly, rabbits were exsanguinated and the thorax was opened to expose the lungs and trachea.…”
Section: Assessment Of Lung Morphometrymentioning
confidence: 99%